Decadal Variability of the MJO and Implications for Southwestern United States Wintertime Precipitation Predictability - Cameron Dong; Yannick Peings; Gudrun Magnusdottir (Geophysical Research Letters)
Abstract The Madden‐Julian Oscillation (MJO) is the dominant source of tropical convective activity on intraseasonal timescales and a significant influence on extratropical weather through remote teleconnections. Here, we investigate decadal variability of the MJO and its boreal winter teleconnections with the Southwestern United States (SWUS) using an ensemble of historical climate simulations, where tropical atmospheric variability is nudged toward reanalysis. Since the beginning of the 21st century, the MJO has been associated with a wavenumber‐5 zonal teleconnection pattern that propagates along the jet stream waveguide. This coupling is absent in the prior two decades, causing significant differences in the Southwestern United States precipitation response. These changes also result in vastly different windows of opportunity for S2S predictability during each period. This decadal variability is potentially associated with the change from a positive to negative Interdecadal Pacific Oscillation, as well as the global warming signal.